Redescription of Lestidiops distans (Ege, 1953) and comments on Lestidiops cadenati (Maul, 1962) from the eastern Atlantic Ocean (Teleostei: Aulopiformes) - Ho, Hsuan-Ching; Tsai, Sung-Yu (Zootaxa, 2023)
The paralepidid species Lestidiops distans (Ege, 1953) is redescribed on the basis of adult specimens collected from the eastern Atlantic Ocean. Observations on the holotype, a detailed description, and full data of the adults are provided. The complete lateral line running to the caudal fin base found in L. distans is a rare condition, with only some species in the family possessing this character. The distribution range of L. distans, from Senegal (14°N) to Namibia (22°S) along the coastline of the eastern Atlantic Ocean, is revised accordingly. Comments on a congener, Lestidiops cadenati (Maul, 1962), that co-occurs in the western Atlantic are provided.